UPAYA MENINGKATKAN KETERAMPILAN MEMBACA WACANA BERAKSARA BALI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK-PAIR-SHARE - Perni, Ni Nyoman (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2018)
The main objectives of the study were: (1) improving the reading skills of Balinese-language discourse in class IX B4 Singaraja Public Middle School 6 semester 2018/2019 academic year, and (2) knowing the responses of class IX B4 Singaraja Public Middle School 6 semester academic year 2018/2019 towards the application of the Think-Pair-Share Cooperative learning model. This research is a classroom action research consisting of two cycles. Each cycle consists of 4 stages, namely: planning, action, observation / evaluation, and reflection. The subjects of this study were class IX B4 Singaraja Public Middle School 6 2018/2019 academic year as many as 31 students. Data on students' skills in reading Balinese-language discourse was collected through skills tests and data on student responses to the application of learning models collected through questionnaires at the end of cycle II. Data collected was analyzed descriptively. The results showed that: (1) the application of the Think-Pair-Share learning model can improve students' skills in reading Balinese literary discourse, namely from the average value of 79 (good) in the first cycle to 85 (very good) in the second cycle, and (2) student responses to the application of the Think-Pair-Share learning model are classified as very positive. Keywords: Cooperative Think-Pair-Share, Balinese literary discourse.